Medicolegal Aspects of Craniofacial Trauma - Vahidi, Nima; Wang, Weitao; Lee, Thomas; Inman, Jared; Ducic, Yadranko (Facial Plastic Surgery, 2019)
Characterization of complications in facial trauma management is of special interest to practitioners of facial trauma surgery. It is important for facial trauma surgeons to not only understand the standard of care, but also the pitfalls that can expose them to litigation. Litigation within the realm of facial trauma surgery often manifests from issues with poor communication, inadequate informed consent processes, and poor surgical management. In this analysis, we comprehensively examine malpractice litigation in facial trauma surgery, and outline important factors for surgeons to consider in the care of this patient population. It is important for facial trauma surgeons to understand medicolegal issues within their scope of practice. These include principles of informed consent, state regulated statutes of limitation, and Emergency Medical Treatment and Active Labor Act laws. This analysis emphasizes the importance of exercising appropriate patient care, understanding the indications for surgery, and seeking counsel when necessary.
Keywords: medicolegal; craniofacial trauma; facial plastic surgery; medical malpractice